A performance‐based payment: Signaling the quality of a credence good. (15th February 2021) - Berg, Nathan; Kim, Jeong‐Yoo; Seon, Ilgyun
Abstract : We consider credence goods. A typical example of a credence good is an expert service. Experts often offer rebates contingent on their client's failure or bonus payments contingent on their client's success. This paper provides a different rationale for performance‐based payments than reducing moral hazard. We show that a performance‐based payment can be a signal of the seller's ability. Due to different success rates across expert abilities, a high‐ability expert can commit to offering larger indemnity payments contingent on a client's failure or smaller bonus payments contingent on a client's success. Thus, high quality is signaled by performance‐based pricing.